ADAPTATION OF MARKETING STRATEGIES OF UKRAINIAN ENTERPRISES IN THE DIGITAL ENVIRONMENT - KUZMYNCHUK Nataliіa; PYSAREVSKA, Hanna; DOROKHOV, Ali Tagmasyp ohly (Herald of Khmelnytskyi National University. Economic sciences, 2025)
This study investigates the adaptation of enterprise marketing strategies in the digital environment, emphasizing the integration of digital technologies, organizational readiness, and proactive management to enhance competitiveness and resilience. The research addresses the need for a comprehensive mechanism that combines human capital development, digital transformation, and strategic planning to enable enterprises to respond effectively to rapidly changing market conditions and uncertainty. Adapting marketing strategies in the digital context requires not only the implementation of new communication channels but also structural and functional transformation of marketing management systems. Key elements include personalized customer communication, big data and predictive analytics, marketing automation, CRM and ERP systems, and a focus on customer experience (CX). Sustainable and socially responsible practices are also embedded to meet growing consumer demand for ecological responsibility and corporate accountability. The study identifies essential directions for strategic adaptation: aligning marketing objectives with enterprise goals, fostering flexible organizational structures and innovation-oriented culture, providing economic support through budgeting and digital investment, developing robust digital infrastructure, implementing risk management and scenario planning under volatile conditions, and establishing monitoring and control systems for real-time performance evaluation. Human capital is emphasized as a critical driver of transformation, with digital skills, creative potential, and proactive thinking being central. Employee training, knowledge-sharing, and talent retention strategies, alongside supportive leadership and corporate culture, facilitate successful adoption of innovative approaches. A phased implementation approach is proposed, including auditing current strategies, stakeholder alignment, selection and integration of digital tools, pilot testing, scaling of effective solutions, and continuous performance monitoring using KPIs such as CAC, CLV, digital engagement rate, and ROI. Special attention is given to high-turbulence and wartime conditions, which limit resources but accelerate innovation and digital adoption. Digitalization acts both as a survival tool and a strategic growth driver, enabling market entry, logistics optimization, and stronger partnerships. The proposed mechanism ensures flexibility, scalability, and alignment with sustainable development principles. The study concludes that effective adaptation of enterprise marketing strategies in the digital era requires a systematic, proactive approach integrating foresight, organizational readiness, economic feasibility, and technological support. The mechanism offers practical guidance for enhancing market positioning, resilience, and customer-centric performance, with prospects for sector-specific models, AI applications, and digital maturity benchmarks.